2021
DOI: 10.3389/fpsyg.2021.716998
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the COVID-19 Pandemic Lockdown on Eating, Body Image, and Social Media Habits Among Women With and Without Symptoms of Orthorexia Nervosa

Abstract: The COVID-19 pandemic is negatively impacting people’s mental health worldwide. The current study examined the effects of COVID-19 lockdown on adult women’s eating, body image, and social media habits. Furthermore, we compared individuals with and without signs of orthorexia nervosa, a proposed eating disorder. Participants were 143 women, aged 17–73 years (M = 25.85, SD = 8.12), recruited during a COVID-19 lockdown in Canada from May-June 2020. Participants completed self-report questionnaires on their eating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(62 reference statements)
0
9
0
1
Order By: Relevance
“…This may have brought forth concerns of gaining weight, which is common in people with EDs [ 25 , 91 ], and increased the symptoms of EDs [ 90 ] and related behaviors such as EE. Third, the immense increase in social media usage during the pandemic may have led to raised worries regarding body appearance and disordered eating [ 92 94 ]. Fourth, limiting grocery trips and food access may have resulted in food insecurity, worries about the availability of food, and hoarding that are related to urges to binge [ 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have brought forth concerns of gaining weight, which is common in people with EDs [ 25 , 91 ], and increased the symptoms of EDs [ 90 ] and related behaviors such as EE. Third, the immense increase in social media usage during the pandemic may have led to raised worries regarding body appearance and disordered eating [ 92 94 ]. Fourth, limiting grocery trips and food access may have resulted in food insecurity, worries about the availability of food, and hoarding that are related to urges to binge [ 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a related line of research has examined pandemic-induced stress and food-related mental health [ 62 , 63 , 64 , 65 ]. Previous research has revealed a wide range of psychosocial impacts of infectious disease that may produce fear in the community or individuals in relation to getting sick or dying, or feeling helpless or stigmatised [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It contributed to the appearance and exacerbation of depression, anxiety, stress, psychological distress, post-traumatic stress disorder, and sleep disturbances (especially insomnia), among others [ 27 , 28 , 29 , 30 ]. Moreover, the pandemic caused the exacerbation of various ED, including increasing the tendency of orthorexia nervosa, which greatly worsened the mental health of individuals with these disorders [ 31 , 32 ]. Most of our respondents (over 80%) reported that the pandemic caused a general deterioration in the quality of their life.…”
Section: Discussionmentioning
confidence: 99%